Single-centre, single-blind, randomized, active-controlled phase-3 non-inferiority study to investigate the safety and efficacy of the cardioplegic solution Cardioplexol™ - Tevaearai Stahel, Hendrik T.; Weiss, Gabriel; Landowski, Peter; Folkmann, Sandra; Harrer, Marieluise; Voet, Bernard; Grabenwöger, Martin (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesEffective and reliable cardioplegic cardiac arrest is crucial for maximizing myocardial protection and preserving postoperative contractile function. Aim of this study was to demonstrate, in line with an ongoing European registration procedure, the efficacy and safety of the new Cardioplexol™ solution.MethodsSingle-centre, single-blind, randomized, active-controlled phase-3 non-inferiority trial comparing Cardioplexol™ and Buckberg solutions during cardiac surgery. Patients planed for elective CABG, valve surgery and/or aortic root surgery, were considered eligible after meeting all inclusion and exclusion criteria. Peak troponin-T (TnT) during the first 24 h post-reperfusion was defined as primary endpoint. Intraoperative and ICU-related secondary endpoints were also evaluated, as were safety endpoints.ResultsOut of 248 operated patients, 226 (100 Cardioplexol™, 126 Buckberg) were considered for per-protocol analysis. Peak-TnT was similar in both groups (0.77 vs. 0.78 ng/ml) and non-inferiority of Cardioplexol™ was confirmed. Delay before complete cardiac arrest (11 vs. 71 s, p < 0.001) and cross-clamp time (51.2 vs. 60.7 min, p < 0.001) were shorter after Cardioplexol™. The defibrillation rate was also significantly reduced (10% vs. 52%, p < 0.001). Although not statistically significant, cumulative dose of catecholamines within 24 h postreperfusion (6,202 vs. 7,170 µg/kg, p = 0.07), and ICU stay (38.1 vs. 44.0 h, p = 0.110) also appeared reduced after Cardioplexol™. Mortality was lower after Cardioplexol™ (1 pt. vs. 5 pts.). Safety parameters were comparable in both groups.ConclusionEfficacy and safety of Cardioplexol™ were demonstrated.Clinical Trial Registrationhttps://www.clinicaltrialsregister.eu/ctr-search/trial/2011-004198-10/results, Eudra CT-No: 2011-004198-10.